Nerve Integrity Monitor Responses to Direct Facial Nerve Stimulation During Facial Nerve Decompression Surgery Can Predict Postoperative Outcomes. Issue 5 (June 2020) - Yamagishi, Tatsuya; Ohshima, Shinsuke; Yagi, Chihiro; Kitazawa, Meiko; Nonomura, Yoriko; Izumi, Shuji; Morita, Yuka; Takahashi, Kuniyuki; Horii, Arata
Abstract : Objective: To test whether the threshold of nerve integrity monitor (NIM) responses during facial nerve decompression surgery can predict the postoperative outcome. Study Design: Retrospective study. Setting: University hospital. Patients: Twenty peripheral facial palsy patients who underwent transmastoid decompression surgery. Intervention: During decompression surgery, thresholds of NIM responses were measured via direct facial nerve stimulation at three sites: the geniculate ganglion (GG), the second genu (2 nd G), and the stylomastoid foramen. Main Outcome Measures: Facial nerve function was evaluated before and 6 months after surgery using the Yanagihara grading score (maximum score = 40 points). Complete recovery was defined as an improvement of the grading score to ≥ 36 points without synkinesis. Variables including age, sex, disease (Bell's palsy or Ramsay Hunt syndrome), time after onset, Yanagihara grading score, and electroneurography before surgery, and the thresholds of NIM responses during surgery were compared in the complete and incomplete recovery groups. NIM responders were defined as those exhibiting a NIM response of < 1.5 mA at any site. Postoperative Yanagihara grading scores in NIM responders and NIM nonresponders were compared. Results: No variables differed significantly in the complete and incomplete recovery groups before surgery. NIM response thresholds in the complete recovery group at the GG and the 2nd G were significantly lower than the corresponding thresholds in the incomplete recovery group. The postoperative Yanagihara grading scores of NIM responders were significantly better than those of NIM nonresponders. Conclusion: NIM responses to intraoperative direct facial nerve stimulation were useful for predicting outcomes after decompression surgery.